Measurement of palliative care competencies using PALCOM instrument (Journal of Health Sciences, 2024)
Introduction: An essential component of any profession is competent and confident staff. In palliative care, a wellrounded approach and versatile knowledge of staff and students are of great importance. Measuring these competencies is very important for the development of palliative care and health care.Methods: Measurement of competencies in palliative care by analyzing existing instruments and questions in palliative care. Process of developing a new instrument for measurement of competencies in palliative care PALCOM, using cross-sectional methodology with nurses from Bosnia and Herzegovina.Results: The results are presenting findings of research done with nurses from BIH using two main variables: Years of work experience and level of education of the participants. Main difference is between the two competencies: Pain assessment and management, education, and care for the patient’s family regarding the level of education.Conclusion: The need for measuring competencies is evident in the daily evolution of palliative care, community-based palliative care, hospice care, and subspecialized palliative care. There is no questionnaire that can measure all competencies, but the use of the general competencies in the PALCOM questionnaire can cover this area with the measurement of different domains and the competencies specific to these domains.